Development of Silver-Meal Heuristic Method for Medium Voltage Network Maintenance Material Management of PT PLN (Persero) - Rahmatullah, Deka; Diawati, Lucia; Sukoyo, Sukoyo (ITB Graduate School Conference, 2025)
PT PLN (Persero) carries out distribution network maintenance activities to ensure the reliability of the electricity distribution system. The material distribution system for maintenance operations at PLN follows a twoechelon structure, consisting of deliveries from suppliers to the Customer Service Implementation Unit (UP3), and subsequently to the Customer Service Units (ULP). This study aims to develop a distribution model for medium- and lowvoltage maintenance materials that considers both transportation and storage costs. The problem is formulated as a Binary Non-Linear Programming (BNLP) model, which is inherently complex and computationally intensive. To address this, a heuristic approach based on the Silver-Meal method is proposed, offering a relatively fast solution to the BNLP model, although it does not always guarantee global optimality. Since the traditional Silver-Meal method does not account for transportation costs, modifications are introduced in this study. The modified Silver-Meal heuristic is applied to the two-echelon distribution problem to evaluate and demonstrate the effectiveness of the proposed approach.